Risk of occupational exposure to blood-borne pathogens in paramedics - Maria Gańczak; Katarzyna Topczewska (Medycyna Pracy, 2018)
Paramedics constitute a group of professionals who are constantly exposed to potentially infectious biological material through frequent and close contact with patients, possibly resulting in occupationally acquired infections. The paper’s objective has been to assess the occupational risk regarding blood-borne infections and identify preventive measures used among paramedics worldwide, on the basis of the related literature review. The literature search, covering the period 1987–2017, was performed using PubMed, Elsevier, Springer and Google Scholar databases. A comparative analysis of blood exposure was conducted and the report of such events and the use of personal protective equipment among paramedics in Poland and other countries worldwide was developed. The data on occupational blood exposures among paramedics is sparse. The resulting comparisons obtained in various scientific studies are difficult due to diverse data collection methods, influencing the resulting consistency. Additionally, there were some methodological errors found in previously published studies, such as selection bias. The percentage rate of paramedics exposed to blood in the last 12 months varies from 22% in the USA to 63% in Thailand; in Poland that rate fluctuates widely, ranging between 14–78%. Paramedics are frequently exposed to blood while performing their duties, but almost 50% of paramedics do not report any exposure which is mitigated by the systematic use of personal protective equipment: gloves are regularly used by 53–98% of paramedics, masks and goggles are worn by 33–62% of them. This fact puts the paramedics group at risk of blood-borne infections. Therefore, there is an urgent need to conduct further, methodologically correct, multi-center studies to accurately assess occupational blood exposure in paramedics. Med Pr 2018;69(6):685–694